Long-Term Impacts of Alternative Approaches to Increase Schooling : Evidence from a Scholarship Program in Cambodia - Barrera-Osorio, Felipe (World Bank, Washington, DC, 2018)
This paper reports on a randomized experiment to investigate the long-term effects of a primary school scholarship program in rural Cambodia. In 2008, fourth-grade students in 207 randomly assigned schools (103 treatment, 104 control) received scholarships based on the students' academic performance in math and language or their level of poverty. Three years after the program's inception, an evaluation showed that both types of scholarship recipients had more schooling than nonrecipients; however, only merit-based scholarships led to improvements in cognitive skills. This new study reports impacts, nine years after program inception, on the educational attainment, cognitive skills, socioemotional outcomes, socioeconomic status and well-being, and labor market outcomes of individuals who are, on average, 21 years old. The results show that both types of scholarships led to higher long-term educational attainment (about 0.21-0.29 grade level), but only merit-based scholarships led to improvements in cognitive skills (0.11 standard deviation), greater self-reported well-being (0.18 standard deviation), and employment probability (3.4 percentage points). Neither type of scholarship increased socioemotional skills. The results also suggest that there are labeling effects: the impacts of the scholarship types differ even for individuals with similar characteristics.